Ten species of Culicoides Latreille (Diptera: Ceratopogonidae) newly recorded from Thailand - Thepparat, Arunrat; Bellis, Glenn; Ketavan, Chitapa; Ruangsittichai, Jiraporn; Sumruayphol, Suchada; Apiwathnasorn, Chamnarn (Zootaxa, 2015)
A survey of biting midges in animal sheds, mangroves and beaches along the Andaman coastal region in southern Thailand between April 2012 and May 2013 collected 10 species of Culicoides which were not previously known from Thailand. These new records are C. arenicola, C. flavipunctatus, C. hui, C. kinari, C. kusaiensis, C. parabubalus, C. quatei, C. spiculae, C. pseudocordiger and C. tamada. An updated checklist of species of Culicoides reported from Thailand is provided.